Negative news dominates fast and slow brain responses and social judgments even after source credibility evaluation - Julia Baum; Rasha Abdel Rahman (NeuroImage, 2021)
Remedies to counter the impact of misinformation are in high demand, but little is known about the neuro-cognitive consequences of untrustworthy information and how they can be mitigated. In this preregistered study, we investigated the effects of social-emotional headline contents on social judgments and brain responses and whether they can be modulated by explicit evaluations of the trustworthiness of the media source. Participants (N = 30) evaluated –and clearly discerned– the trustworthiness of news sources before they were exposed to person-related news headlines. Despite this intervention, social judgments and brain responses were dominated largely by emotional headline contents. Results suggest differential effects of source credibility might depend on headline valence. Electrophysiological indexes of fast emotional and arousal-related brain responses, as well as correlates of slow evaluative processing were enhanced for persons associated with positive headline contents from trusted sources, but not when positive headlines stemmed from distrusted sources. In contrast, negative headlines dominated fast and slow brain responses unaffected by explicit source credibility evaluations. These results provide novel insights into the brain mechanisms underlying the “success” of emotional news from untrustworthy sources, suggesting a pronounced susceptibility to negative information even from distrusted sources that is reduced for positive contents. The differential pattern of responses to misinformation in mind and brain sheds light on the cognitive mechanisms underlying the processing of misinformation and possible strategies to avoid their potentially detrimental effects.